AgCuTe-based composite thermoelectric material and preparation method thereof

By in situ composite SnTe in AgCuTe, a layered scattering defect structure was constructed, which solved the problem of high thermal conductivity of AgCuTe-based thermoelectric materials and significantly improved its thermoelectric performance.

CN119677392APending Publication Date: 2025-03-21ANYANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411807842.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The intrinsic thermal conductivity of AgCuTe-based thermoelectric materials is relatively high, which limits the further improvement of their thermoelectric properties.

Method used

By in situ composite SnTe in AgCuTe, a stratified scattering defect structure is constructed to inhibit the propagation of all frequency phonons, thereby reducing thermal conductivity.

Benefits of technology

The thermal conductivity of AgCuTe-based materials is significantly reduced, its thermoelectric properties are improved, and the thermoelectric superiority zT is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677392A_ABST
    Figure CN119677392A_ABST
Patent Text Reader

Abstract

The invention discloses an AgCuTe-based composite thermoelectric material and a preparation method thereof, the AgCuTe-based composite thermoelectric material is AgCuTe-x wt% SnTe, and x is equal to 1-7. The preparation method comprises the following steps: 1) weighing Ag powder, Cu powder, Te powder and polycrystalline SnTe according to a stoichiometric ratio; and 2) after mixing, filling the mixture into a graphite crucible, putting the graphite crucible into a vacuumized quartz tube, and sintering in a muffle furnace to obtain a cast ingot. And 3) ball-milling the sintered sample into powder, and carrying out spark plasma sintering to obtain the compact AgCuTe-based composite block material. Compared with a conventional material compounding method, the method has the advantages that SnTe is compounded in the AgCuTe in situ, so that a multi-scale defect structure is more favorably constructed, and the maximum phonon scattering efficiency is obtained. According to the optimization method provided by the invention, the heat conductivity of the liquid-like material AgCuTe is further reduced, the thermoelectric figure of merit zT of the material is improved, and a foundation is laid for further development and application of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of new energy materials, and in particular to an AgCuTe-based composite thermoelectric material and a preparation method thereof. Background Art

[0002] With the rapid development of the economy, the problems of energy shortage and environmental pollution are becoming more and more serious. Faced with such problems, on the one hand, people are accelerating the development of new renewable energy sources, such as solar energy, wind energy, hydropower, geothermal energy, nuclear energy, etc., to replace traditional fossil energy. On the other hand, researchers are also working hard to improve the utilization rate of energy to achieve effective multi-level utilization of energy. Thermoelectric technology can not only effectively utilize waste heat to realize the conversion of thermal energy into electrical energy and improve the effective utilization rate of energy. It can also use electrical energy to achieve the purpose of solid-state refrigeration. With the advantages of simplicity, sensitivity, high stability and pollution-free nature of thermoelectric power generation and refrigeration technology, it has been widely used in special power supplies, small refrigerators, semiconductor refrigeration and smart wearables in aerospace.

[0003] The application of thermoelectric technology depends on thermoelectric materials with good performance. The energy conversion efficiency of thermoelectric materials depends on the dimensionless thermoelectric figure of merit. z , z = S 2 σT / κ ,in S is the Seebeck coefficient, σ is the conductivity, κ is the thermal conductivity, T is the absolute temperature. S 2 σ , called power factor PF , which determines the electrical properties of the material. The various thermoelectric parameters are coupled to each other and it is difficult to improve them simultaneously. The ideal thermoelectric material should have a high power factor and low thermal conductivity to make z Maximize value.

[0004] Liquid-like thermoelectric materials have the characteristics of "phonon liquid, electron crystal", which meet the requirements of high power factor and low thermal conductivity of ideal thermoelectric materials. They are a type of thermoelectric material system that has attracted widespread attention. Among liquid-like materials, AgCuTe-based thermoelectric materials have the advantages of non-toxic elements and good electrical transport performance. AgCuTe has excellent thermoelectric properties, but compared with other liquid-like materials such as Ag9GaSe6, its intrinsic thermal conductivity is relatively high, which limits the further improvement of its thermoelectric performance.

[0005] Therefore, reducing the thermal conductivity of AgCuTe is a challenge and the key to breaking through its existing thermoelectric performance. Summary of the invention

[0006] In view of the above problems, the purpose of the present invention is to provide a preparation method for improving the thermoelectric performance of AgCuTe thermoelectric materials by constructing a multi-scale microscopic defect structure in the material. Although conventional material composite methods can mix the matrix material and the composite material evenly, it is difficult to construct a multi-scale defect structure, which is not conducive to suppressing the propagation of multi-range phonons. The present invention can construct a layered scattering defect structure to suppress the propagation of full-frequency phonons and obtain the maximum phonon scattering efficiency by in-situ composite SnTe in AgCuTe. Thereby, the thermoelectric performance of the matrix material is improved by significantly reducing the thermal conductivity.

[0007] The technical solution adopted by the present invention to solve the above-mentioned problems is: An AgCuTe-based composite thermoelectric material, characterized in that: the AgCuTe-based composite thermoelectric material is AgCuTe- x wt% SnTe, where x The range is 1-7, x wt% indicates the mass fraction of SnTe in AgCuTe.

[0008] The present invention also provides a method for preparing the AgCuTe-based composite thermoelectric material, comprising the following steps: 1) By AgCuTe – x wt% SnTe stoichiometric ratio of Ag powder, Cu powder, Te powder, high-purity solid single substance and polycrystalline SnTe are weighed and mixed uniformly; 2) The raw materials mixed evenly in step 1) are placed in a graphite crucible, and then placed in a vacuum quartz tube, and sintered into an ingot in a muffle furnace; 3) Place the ingot in a ball mill filled with argon and crush it into fine powder; 4) The powder is subjected to spark plasma sintering (SPS) to obtain a dense AgCuTe-based composite thermoelectric bulk material.

[0009] Furthermore, in the step 1), the purity of Ag powder is 99.95 wt% to 99.999 wt%, the purity of Cu powder is 99.99 wt% to 99.999 wt%, the purity of Te powder is 99.99 wt% to 99.999 wt%, and the polycrystalline SnTe uses high-purity polycrystalline SnTe with a purity of 99.9 wt% to 99.999 wt%.

[0010] Furthermore, in step 2), the vacuum degree of the sealed quartz tube is 10 -1 Pa.

[0011] Furthermore, during sintering in step 2), the material is slowly heated from room temperature to 673 - 773 K for 11-12 h, then heated to 1273 - 1373 K for 4.5 -5.5 h, kept at this temperature for 11 -13 h, and finally slowly cooled to room temperature.

[0012] Preferably, during sintering in step 2), the sintered product is slowly heated from room temperature to 723 K for 12 h, then heated to 1323 K for 5 h, kept at this temperature for 12 h, and finally slowly cooled to room temperature.

[0013] Furthermore, in step 3), the rotation speed of the ball mill is 200-300 rpm, and the ball milling time is 20-40 min.

[0014] Preferably, in step 3), the rotation speed of the ball mill is 250 rpm, and the ball milling time is 30 min.

[0015] Furthermore, in step 4), the temperature of the spark plasma sintering is 518-578 K, the pressure is 45-55 MPa, and the sintering time is 4-6 min.

[0016] Preferably, in step 4), the spark plasma sintering is carried out at a temperature of 548 K, a pressure of 50 MPa, and a time of 5 min.

[0017] The preparation method of the AgCuTe-based composite thermoelectric material in the present invention is mainly characterized by in-situ composite SnTe during the synthesis process of AgCuTe, that is, polycrystalline SnTe and raw materials Ag, Cu and Te are weighed and melted based on stoichiometric ratios. Compared with conventional material composite methods, the in-situ composite method in this invention is the whole process of SnTe participating in the synthesis of AgCuTe, which is more conducive to constructing various defect structures from atomic scale to micro- and nano-scale, and can reduce the thermal conductivity of AgCuTe-based materials and improve their thermoelectric performance.

[0018] Compared with the prior art, the present invention has the following advantages: 1. The present invention is the first to in-situ composite SnTe in AgCuTe to inhibit phonon propagation in the full frequency range and effectively reduce thermal conductivity.

[0019] 2. The method adopted in the present invention maintains the electrical transport performance of the composite thermoelectric material substantially unchanged, and significantly improves the thermoelectric performance of AgCuTe by reducing the thermal conductivity.

[0020] 3. The preparation method, production process and production equipment for in-situ composite SnTe in AgCuTe provided by the present invention are simple and have good controllability and repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 This is a transmission electron microscope image of the AgCuTe –3wt% SnTe composite thermoelectric material.

[0023] Figure 2 AgCuTe – x wt% SnTe( x = 0,1,3,5,7) conductivity plot of composite thermoelectric materials as a function of temperature.

[0024] Figure 3 AgCuTe – x wt% SnTe( x = 0,1,3,5,7) Seebeck coefficient diagram of composite thermoelectric materials as a function of temperature.

[0025] Figure 4 AgCuTe – x wt% SnTe( x = 0,1,3,5,7) Power factor diagram of composite thermoelectric materials changing with temperature.

[0026] Figure 5 AgCuTe – x wt% SnTe( x = 0,1,3,5,7) Thermal conductivity diagram of composite thermoelectric materials as a function of temperature.

[0027] Figure 6 AgCuTe – x wt% SnTe( x = 0,1,3,5,7) Thermoelectric figure of merit of composite thermoelectric materials as a function of temperature z picture. DETAILED DESCRIPTION

[0028] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0029] In the present invention, the purity of Ag powder is 99.95 wt% to 99.999 wt%, the purity of Cu powder is 99.99 wt% to 99.999 wt%, the purity of Te powder is 99.99 wt% to 99.999 wt%, and the polycrystalline SnTe adopts high-purity polycrystalline SnTe with a purity of 99.9 wt% to 99.999 wt%.

[0030] Example 1 An AgCuTe-based composite thermoelectric material (AgCuTe – 1wt% SnTe is used as an example below) is prepared as follows: 1) Weigh the single-element raw materials Ag powder, Cu powder, and Te powder according to the stoichiometric ratio of 1:1:1, then mix the single-element solid raw materials and polycrystalline SnTe accounting for 1% of the total weight of the single-element solid raw materials, put them into a graphite crucible, and put them into a quartz tube. Vacuum seal in a vacuum tube sealing machine with a vacuum degree of 10 -1 Pa.

[0031] 2) The sealed quartz tube was slowly heated from room temperature to 723 K in a muffle furnace for 12 h, then heated to 1323 K for 5 h, maintained at 1323 K for 12 h, and finally slowly cooled to room temperature.

[0032] 3) The densely sintered ingot was placed in a ball mill filled with argon and ball-milled into nanopowder at 250 rpm for 30 min.

[0033] 4) The obtained powder was loaded into a graphite mold and densified by SPS at 548 K and 50 MPa for 5 min to finally obtain a bulk thermoelectric material AgCuTe – 1wt% SnTe with a density greater than 98%.

[0034] The electrical conductivity, Seebeck coefficient, power factor, thermal conductivity and z Value Figure 2-Figure 6 The conductivity at room temperature is 12 × 10 4 S m -1 , the thermal conductivity is 1.35 W m -1 K -1 At 500 K the phase changes to β The thermal conductivity of the phase decreased to 0.58 W m -1 K -1 , and shows no dependence on temperature, which is a typical liquid-like heat transport characteristic. z 0.80 at 723 K.

[0035] Example 2 An AgCuTe-based composite thermoelectric material (AgCuTe – 3wt% SnTe is used as an example below) is prepared as follows: 1) Weigh the single-element raw materials Ag powder, Cu powder, and Te powder according to the stoichiometric ratio of 1:1:1, then mix the single-element solid raw materials and polycrystalline SnTe accounting for 3% of the total weight of the single-element solid raw materials, put them into a graphite crucible, and put them into a quartz tube. Vacuum seal in a vacuum tube sealing machine with a vacuum degree of 10 -1 Pa.

[0036] 2) The sealed quartz tube was slowly heated from room temperature to 723 K in a muffle furnace for 12 h, then heated to 1323 K for 5 h, maintained at 1323 K for 12 h, and finally slowly cooled to room temperature.

[0037] 3) The densely sintered ingot was placed in a ball mill filled with argon and ball-milled into nanopowder at 250 rpm for 30 min.

[0038] 4) The obtained powder was loaded into a graphite mold and densified by SPS at 548 K and 50 MPa for 5 min to finally obtain a bulk thermoelectric material AgCuTe – 3wt% SnTe with a density greater than 98%.

[0039] The high-resolution transmission electron microscopy image of the AgCuTe-3wt% SnTe thermoelectric material obtained in this example is shown in Figure 1 High-resolution transmission electron microscopy shows that atomic-scale and micro-nanoscale defect structures, such as heterophase interfaces and additional grain boundaries, are constructed in the matrix material through in-situ recombination.

[0040] The electrical conductivity, Seebeck coefficient, power factor, thermal conductivity and z Value Figure 2-Figure 6 As shown, its thermal conductivity at 300 K is 0.90 W m -1 K -1 , compared with the thermal conductivity of AgCuTe matrix of 1.35 W m -1 K -1 The power factor is basically unchanged compared with the substrate, and its thermoelectric figure of merit is z It reaches 1.1 at 723 K, which is nearly 40% higher than 0.80 of AgCuTe matrix.

[0041] Example 3 An AgCuTe-based composite thermoelectric material (AgCuTe–5wt% SnTe is used as an example below) is prepared as follows: 1) Weigh the single-element raw materials Ag powder, Cu powder, and Te powder according to the stoichiometric ratio of 1:1:1, then mix the single-element solid raw materials and polycrystalline SnTe accounting for 5% of the total weight of the single-element solid raw materials, put them into a graphite crucible, and put them into a quartz tube. Vacuum seal in a vacuum tube sealing machine, and the vacuum degree is about 10 -1 Pa.

[0042] 2) The sealed quartz tube was slowly heated from room temperature to 723 K in a muffle furnace for 12 h, then heated to 1323 K for 5 h, maintained at 1323 K for 12 h, and finally slowly cooled to room temperature.

[0043] 3) The densely sintered ingot was placed in a ball mill filled with argon and ball-milled into nanopowder at 250 rpm for 30 min.

[0044] 4) The obtained powder was loaded into a graphite mold and densified by SPS at 548 K and 50 MPa for 5 min to finally obtain a bulk thermoelectric material AgCuTe – 5wt% SnTe with a density greater than 98%.

[0045] The electrical conductivity, Seebeck coefficient, power factor, thermal conductivity and z Value Figure 2-Figure 6 As shown, its thermal conductivity at 300 K is 1.10 W m - 1 K -1 , compared with the thermal conductivity of AgCuTe matrix of 1.35 W m -1 K -1 The power factor is basically unchanged compared with the substrate, and its thermoelectric figure of merit is z It reaches 1.05 at 723 K, which is 30% higher than 0.80 of AgCuTe matrix.

[0046] Example 4 An AgCuTe-based composite thermoelectric material (AgCuTe-7wt% SnTe is used as an example below) is prepared as follows: 1) Weigh the single-element raw materials Ag powder, Cu powder, and Te powder according to the stoichiometric ratio of 1:1:1, then mix the single-element solid raw materials and polycrystalline SnTe accounting for 7% of the total weight of the single-element solid raw materials, put them into a graphite crucible, and put them into a quartz tube. Vacuum seal in a vacuum tube sealing machine, and the vacuum degree is about 10-1 Pa.

[0047] 2) The sealed quartz tube was slowly heated from room temperature to 723 K in a muffle furnace for 12 h, then heated to 1323 K for 5 h, maintained at 1323 K for 12 h, and finally slowly cooled to room temperature.

[0048] 3) The densely sintered ingot was placed in a ball mill filled with argon and ball-milled into nanopowder at 250 rpm for 30 min.

[0049] 4) The obtained powder was loaded into a graphite mold and densified by SPS at 548 K and 50 MPa for 5 min to finally obtain a bulk thermoelectric material AgCuTe – 7wt% SnTe with a density greater than 98%.

[0050] The electrical conductivity, Seebeck coefficient, power factor, thermal conductivity and z Value Figure 2-Figure 6 As shown, its thermal conductivity at 300 K is 1.18 W m -1 K -1 , compared with the thermal conductivity of AgCuTe matrix of 1.35 W m -1 K -1 The power factor is basically unchanged compared with the substrate, and its thermoelectric figure of merit is z It reaches 0.96 at 723 K, which is nearly 20% higher than 0.80 of AgCuTe matrix.

[0051] Example 5 An AgCuTe-based composite thermoelectric material (AgCuTe – 3wt% SnTe is used as an example below) is prepared as follows: 1) Weigh the single-element raw materials Ag powder, Cu powder, and Te powder according to the stoichiometric ratio of 1:1:1, then mix the single-element solid raw materials and polycrystalline SnTe accounting for 3% of the total weight of the single-element solid raw materials, put them into a graphite crucible, and put them into a quartz tube. Vacuum seal in a vacuum tube sealing machine with a vacuum degree of 10 -1 Pa.

[0052] 2) The sealed quartz tube was slowly heated from room temperature to 673 K in a muffle furnace for 11 h, then heated to 1273 K for 4.5 h, maintained at 1273 K for 13 h, and finally slowly cooled to room temperature.

[0053] 3) The densely sintered ingot was placed in a ball mill filled with argon and ball-milled into nanopowder at 200 rpm for 40 min.

[0054] 4) The obtained powder was loaded into a graphite mold and densified by SPS at 518 K and 45 MPa for 4 min to finally obtain a bulk thermoelectric material AgCuTe – 3wt% SnTe with a density greater than 98%.

[0055] Example 6 An AgCuTe-based composite thermoelectric material (AgCuTe – 3wt% SnTe is used as an example below) is prepared as follows: 1) Weigh the single-element raw materials Ag powder, Cu powder, and Te powder according to the stoichiometric ratio of 1:1:1, then mix the single-element solid raw materials and polycrystalline SnTe accounting for 3% of the total weight of the single-element solid raw materials, put them into a graphite crucible, and put them into a quartz tube. Vacuum seal in a vacuum tube sealing machine with a vacuum degree of 10 -1 Pa.

[0056] 2) The sealed quartz tube was slowly heated from room temperature to 773 K in a muffle furnace for 12 h, then heated to 1373 K for 5.5 h, maintained at 1373 K for 12 h, and finally slowly cooled to room temperature.

[0057] 3) The densely sintered ingot was placed in a ball mill filled with argon and ball-milled into nanopowder at 300 rpm for 20 min.

[0058] 4) The obtained powder was loaded into a graphite mold and densified by SPS at 578 K and 55 MPa for 6 min to finally obtain a bulk thermoelectric material AgCuTe – 3wt% SnTe with a density greater than 98%.

[0059] The present invention provides a method for preparing AgCuTe-based composite thermoelectric materials. By constructing a multi-scale defect structure in the AgCuTe matrix, including atomic-scale vacancy defects, nanoscale second-phase precipitates, micro-nanoscale heterophase interfaces and grain boundaries, phonons in the full frequency range are scattered, the thermal conductivity of the matrix material is effectively reduced, and the thermoelectric figure of merit of the matrix material is greatly improved. z .

[0060] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. An AgCuTe-based composite thermoelectric material, characterized in that: The AgCuTe-based composite thermoelectric material is AgCuTe- x wt% SnTe, where x The range is 1-7.

2. The method for preparing the AgCuTe-based composite thermoelectric material according to claim 1, characterized in that The following steps are involved: 1) By AgCuTe – x wt% SnTe stoichiometric ratio of Ag powder, Cu powder, Te powder, high-purity solid single substance and polycrystalline SnTe are weighed and mixed uniformly; 2) The raw materials mixed evenly in step 1) are placed in a graphite crucible, and then placed in a vacuum quartz tube, and sintered into an ingot in a muffle furnace; 3) Place the ingot in a ball mill filled with argon and crush it into fine powder; 4) The powder is subjected to spark plasma sintering to obtain a dense AgCuTe-based composite thermoelectric bulk material.

3. The method for preparing the AgCuTe-based composite thermoelectric material according to claim 2, characterized in that: In the step 1), the purity of Ag powder is 99.95 wt% to 99.999 wt%, the purity of Cu powder is 99.99 wt% to 99.999 wt%, the purity of Te powder is 99.99 wt% to 99.999 wt%, and the polycrystalline SnTe uses high-purity polycrystalline SnTe with a purity of 99.9 wt% to 99.999 wt%.

4. The method for preparing the AgCuTe-based composite thermoelectric material according to claim 2, characterized in that: The vacuum degree of the sealed quartz tube in step 2) is 10 -1 Pa.

5. The method for preparing the AgCuTe-based composite thermoelectric material according to claim 2, characterized in that: During the sintering in step 2), the sintering is performed by slowly heating from room temperature to 673-773 K for 11-12 h, then heating to 1273-1373 K for 4.5-5.5 h, maintaining the temperature for 11-13 h, and finally slowly cooling to room temperature.

6. The method for preparing the AgCuTe-based composite thermoelectric material according to claim 5, characterized in that: During the sintering in step 2), the sintering is performed by slowly heating from room temperature to 723 K for 12 h, then heating to 1323 K for 5 h, keeping at this temperature for 12 h, and finally slowly cooling to room temperature.

7. The method for preparing the AgCuTe-based composite thermoelectric material according to claim 2, characterized in that: In step 3), the rotation speed of the ball mill is 200-300 rpm, and the ball milling time is 20-40 min.

8. The method for preparing the AgCuTe-based composite thermoelectric material according to claim 7, characterized in that: In step 3), the rotation speed of the ball mill is 250 rpm, and the ball milling time is 30 min.

9. The method for preparing the AgCuTe-based composite thermoelectric material according to claim 2, characterized in that: In the step 4), the temperature of the spark plasma sintering is 518-578 K, the pressure is 45-55 MPa, and the sintering time is 4-6 min.

10. The method for preparing the AgCuTe-based composite thermoelectric material according to claim 9, characterized in that: The temperature of the spark plasma sintering in step 4) is 548 K, the pressure is 50 MPa, and the time is 5 min.